Preventing the spread of COVID-19 through environmental design in Thai community hospitals - Waroonkun, Tanut; Prugsiganont, Supuck (Frontiers in Built Environment, 2022)
The unprecedented outbreak of COVID-19 has had a tremendous negative impact on healthcare facilities, especially public hospitals. Thai community hospitals serve as primary care for COVID-19 patients. However, many hospital buildings were constructed in the 1990s and are now becoming outdated. Community hospitals faced many difficulties during the Thailand COVID-19 outbreak. To identify these difficulties this study focused on the physical settings of the community hospital’s outpatient departments (OPD) between 2020 and 2021. Furthermore, the study provided design suggestions for preventing the spread of respiratory infectious diseases. The study used a three-step process of data collection. The first was to observe the physical settings of the OPD buildings of the three hospitals. Secondly, interviews were conducted with thirty healthcare employees: 11 from the first hospital, 11 from the second hospital and 8 from the third hospital. Interviews were transcribed and analyzed using content analysis. Subsequently, the architectural design was produced based on observation and interview analysis. In the third step, the same thirty participants evaluated the architectural design through a focus group. Findings from the interviews led to four themes: 1) factors leading to the accumulation of pathogens, 2) measures for preventing the spread of respiratory diseases, 3) the effect of patient numbers on virus transmission, and 4) suggestions for improving the physical setting of OPDs. The analysis of the four themes led to the preliminary design recommendation, which was evaluated through a focus group, leading to suggestions for the improvement of thirteen areas. The analysis results showed that the participants were satisfied with the architectural design with additional minor recommendations. This study provided originality for the implementation and future development of hospital layout designs that can prevent the spread of COVID-19 throughout Thai community hospitals.